2016
DOI: 10.18295/squmj.2016.16.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reaction between Boric Acid and Phosphine Indicates Boric Acid as an Antidote for Aluminium Phosphide Poisoning

Abstract: Objectives: Aluminium phosphide (AlP) is a fumigant pesticide which protects stored grains from insects and rodents. When it comes into contact with moisture, AlP releases phosphine (PH 3 ), a highly toxic gas. No efficient antidote has been found for AlP poisoning so far and most people who are poisoned do not survive. Boric acid is a Lewis acid with an empty p orbital which accepts electrons. This study aimed to investigate the neutralisation of PH 3 gas with boric acid. Methods: This study was carried out a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Based on in vitro studies, 6-aminonicotinamide showed protective activity in hepatocytes [ 60 ]. Finally, although not fully investigated, boric acid theoretically seems to be a potential antidote by trapping PH 3 [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on in vitro studies, 6-aminonicotinamide showed protective activity in hepatocytes [ 60 ]. Finally, although not fully investigated, boric acid theoretically seems to be a potential antidote by trapping PH 3 [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…One-gram AlP tablets were added to 200 ml of various solvents including distilled water, activated charcoal diluted in distilled water and saturated boric acid solution [ 62 ]. Each solution was used at both normal and acidified pH and separately examined.…”
Section: -Aminonicotinamide (6-an)mentioning
confidence: 99%
“…In addition, activated charcoal can absorb phosphine gas. [6][7][8][9] Although the exact time of toxicity was not known, we performed gastric lavage with potassium permanganate and sodium bicarbonate. Rapid use of activated charcoal and gastric lavage with potassium permanganate and sodium bicarbonate can potentially be used in patients with AlP toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Boric acid is considered as a safe product and its toxicity is unusual (Kaymaz 2015), so we tried in our study to test the possible use of this substance as an antidote for ALP poisoning in rat models, based on the theoretical study of Soltani et al, (2016).…”
Section: Discussionmentioning
confidence: 99%